2019
DOI: 10.1063/1.5128053
|View full text |Cite
|
Sign up to set email alerts
|

Sensing the turbulent large-scale motions with their wall signature

Abstract: This study assesses the capability of extended proper orthogonal decomposition (EPOD) and convolutional neural networks (CNNs) to reconstruct large-scale and very-large-scale motions (LSMs and VLSMs respectively) employing wall-shear-stress measurements in wall-bounded turbulent flows. Both techniques are used to reconstruct the instantaneous LSMs evolution in the flow field as a combination of proper orthogonal decomposition (POD) modes, employing a limited set of instantaneous wall-shear-stress measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 65 publications
(48 reference statements)
1
32
2
Order By: Relevance
“…On the other hand, FCN-POD applies POD only on the output flow fields, using the spatial modes from the training set and predicting the corresponding temporal coefficients using a neural network. This is a development of the model used by Güemes et al (2019), note, however, that, in that study, the domain employed and reconstructed provided a compact POD eigenspectrum, here, the availability of a larger domain in the streamwise and spanwise directions spreads the energy content over a wider set of POD modes. This makes the predictions of temporal coefficients more difficult, especially those associated with the least energetic modes.…”
Section: Summary Of the Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, FCN-POD applies POD only on the output flow fields, using the spatial modes from the training set and predicting the corresponding temporal coefficients using a neural network. This is a development of the model used by Güemes et al (2019), note, however, that, in that study, the domain employed and reconstructed provided a compact POD eigenspectrum, here, the availability of a larger domain in the streamwise and spanwise directions spreads the energy content over a wider set of POD modes. This makes the predictions of temporal coefficients more difficult, especially those associated with the least energetic modes.…”
Section: Summary Of the Methodsmentioning
confidence: 99%
“…The FCN-POD model is built upon the previous work by Güemes et al (2019). In the present work a different neural-network architecture, a fully convolutional one, is used instead of a CNN.…”
Section: Pod-based Predictions With Convolutional Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, machine learning, especially deep learning (LeCun, Bengio & Hinton 2015), has shown remarkable performance. Güemes, Discetti & Ianiro (2019) applied an extended POD and convolutional neural networks, respectively, to reconstruct large- and very large-scale motions in a turbulent channel flow based on the wall shear stress measurement, and showed that the convolutional neural networks performed significantly better than the extended POD. Kim & Lee (2020) used a nine-layer convolutional neural network (CNN) to predict the heat flux at the wall using wall variables (, and ), and showed that the CNN outperformed a linear regression.…”
Section: Introductionmentioning
confidence: 99%